Risk Taking Sexual Behaviors among Antiretroviral Therapy Patients in Lafia, Nigeria; A Cross Sectional Survey. - Bako Ishaku Ara; Audu Esther Solomon; Audu Onyemocho; Araoye Margaret Olabisi (Universiti Kebangsaan Malaysia, 2014)
The HIV Prevalence in Nasarawa State, Nigeria is 7.5% which is above the national average of 4.1%. HIV prevention efforts have however not sufficiently targeted HIV-positive individuals partly due to inadequate data on their risk taking behaviours. The objective of the study was to determine sexual behaviours of Persons living with HIV (PLHIV) receiving antiretroviral therapy at the Dalhatu Araf Specialist Hospital, Lafia, Nigeria.